OP0204 Autophagy and Unfolded Protein Response: A Fine Balance that can Influence the Pathogenesis of Ankylosing Spondylitis and Inflammatory Bowel Disease. (9th June 2015) - Haroon, N.; Guggino, G.; Zhang, Z.; Yee, K.; Abdullah, H.; Alessandro, R.; Raimondo, S.; Triolo, G.; Ciccia, F.
Abstract : Background: We have shown an increase in the unfolded protein response (UPR) with decreased ERAP1 or ERAP2 function in an in vitro system. Similarly UPR has been demonstrated to correlate with onset of disease in the HLA-B27 rat model. UPR has been difficult to demonstrate in the gut of AS patients but autophagy is upregulated. ERAP2 is associated with both AS and inflammatory bowel disease (IBD). Objectives: Here we explore the moderating effect of autophagy on UPR. Specifically we study the impact of suppressing autophagy on UPR. Methods: Lamina Propria Mononuclear cells (LPMC) were isolated from terminal ileal biopsies of 10 AS patients. Autophagy was suppressed with 2 agents anisomycin and 3-MA. In parallel an in vitro system was established with C1R-B27 cells (B-lymphoblastoid cells with stable HLA-B27 expression) and the presence of autophagy in these cells were established with electron microscopy as well as by transfecting these cells with LC3-RFP followed by confocal microscopy. Autophagy was suppressed in C1R-B27 cells using 3-MA. In both LPMC and C1R B27 cells, suppression of autophagy was demonstrated by RT-PCR of appropriate markers. Changes in MHC-I free heavy chain (FHC) expression were tested by HC10 staining and flow cytometry. Changes in UPR following inhibition were tested by XBP1 splicing assay and RT-PCR for BiP, CHOP, PERK, GADD34 and PDIA6. Results: Electron and confocal microscopy demonstrated autophagy in C1R-B27 cells. Autophagy was in a dynamic state in the C1R cells as demonstrated by changes with rapamycin a stimulator of autophagy. Significant suppression of autophagy was noted in both LPMCs and C1R-B27 cells. Following autophagy suppression there was a significant increase in FHC expression in both C1R cells and LPMCs. In parallel we demonstrated increase in UPR markers in both LPMCs and C1R cells. Conclusions: The inability to demonstrate UPR in some in vivo studies could be due to compensation by autophagy. Autophagy and UPR regulate each other and perturbations of this fine balance can influence the pathogenesis of AS and IBD. Disclosure of Interest: None declared